The usefulness of Action-Oriented Simulation Accounting Package (ASAP) as a tool to develop skills / Che Ku Hisam Che Ku Kassim... [et al.] - Che Ku Kassim, Che Ku Hisam; Mohd Nasir, Noor Emilina; Ahmad, Suraya; Wan Mohd Nori, Wan Mohd Nazif; Mod Arifin, Nur Nariza; Zainal@Zakaria, Zaiza Norsuriati (UiTM Cawangan Johor, 2019)
The current business environment is growing at rapid pace. Consequently, it affects a manner in which accounting is practised. The role of accountants is shifted from being mere financial information providers to the ones who are directly and actively involved in different levels of managerial functions. To assist them in fulfilling their responsibilities in a more effective manner, accountants in the era of globalisation need to be equipped with multiple skills and competencies. Therefore, it is the responsibility of the accounting education system to innovatively develop academic approaches that can prepare future accountants for this challenging role. Perhaps, one of such approaches is through the employment of an active-oriented learning method known as the ASAP. The objective of the study is to examine students’ perceptions on the usefulness of the ASAP as an action-oriented learning approach in developing the needful skills of the accounting profession and industry. In achieving the objective, an experiment-based research utilising an online survey using a questionnaire has been conducted on 45 accounting students who have completed a course in accounting software. In general, the results indicate positive perceptions among the students that the ASAP is useful in developing both technical and non-technical skills. The operationalisation of the ASAP helps developing the students’ ability to identify relevant data and apply diverse knowledge within business realms.